Predatory birds and ants partition caterpillar prey by body size and diet breadth. (4th September 2017) - Singer, Michael S.; Clark, Robert E.; Lichter‐Marck, Issac H.; Johnson, Emily R.; Mooney, Kailen A.
Abstract: The effects of predator assemblages on herbivores are predicted to depend critically on predator–predator interactions and the extent to which predators partition prey resources. The role of prey heterogeneity in generating such multiple predator effects has received limited attention. Vertebrate and arthropod insectivores constitute two co‐dominant predatory taxa in many ecosystems, and the emergent properties of their joint effects on insect herbivores inform theory on multiple predator effects as well as biological control of insect herbivores. Here we use a large‐scale factorial manipulation to assess the extent to which birds and ants engage in antagonistic predator–predator interactions and the consequences of heterogeneity in herbivore body size and diet breadth (i.e. the diversity of host plants used) for prey partitioning. We excluded birds and reduced ant density (by 60%) in the canopies of eight northeastern USA deciduous tree species during two consecutive years and measured the community composition and traits of lepidopteran larvae (caterpillars). Birds did not affect ant density, implying limited intraguild predation between these taxa in this system. Birds preyed selectively upon large‐bodied caterpillars (reducing mean caterpillar length by 12%) and ants preyed selectively upon small‐bodied caterpillars (increasing mean caterpillar length by 6%). Birds and ants also partitioned caterpillar prey by diet breadth. Birds reduced the frequency dietary generalist caterpillars by 24%, while ants had no effect. In contrast, ants reduced the frequency of dietary specialists by 20%, while birds had no effect, but these effects were non‐additive; under bird exclusion, ants had no detectable effect, while in the presence of birds, they reduced the frequency of specialists by 40%. As a likely result of prey partitioning by body size and diet breadth, the combined effects of birds and ants on total caterpillar density were additive, with birds and ants reducing caterpillar density by 44% and 20% respectively. These results show evidence for the role of prey heterogeneity in driving functional complementarity among predators and enhanced top‐down control. Heterogeneity in herbivore body size and diet breadth, as well as other prey traits, may represent key predictors of the strength of top‐down control from predator communities. Abstract : This study shows how different groups of insect‐eating predators in a temperate forest effectively suppress their prey by partitioning the prey community. Although birds prey selectively upon large‐bodied, dietary generalist caterpillars, ants prey selectively on small‐bodied, dietary specialist caterpillars. This work suggests that prey heterogeneity is important for effective predator control of herbivores, an important ecosystem service. Photos credit: Christian Skorik and Isaac Lichter‐Marck.